2020
DOI: 10.1111/hepr.13495
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Enhanced Liver Fibrosis test, and combination of the Enhanced Liver Fibrosis and non‐invasive tests for the diagnosis of advanced liver fibrosis in patients with non‐alcoholic fatty liver disease

Abstract: Aim The Enhanced Liver Fibrosis (ELF) test comprises a logarithmic algorithm combining three serum markers of hepatic extracellular matrix metabolism. We aimed to evaluate the performance of ELF for the diagnosis of liver fibrosis and to compare it with that of liver stiffness measurement (LSM) by FibroScan in non‐alcoholic fatty liver disease. Methods ELF cut‐off values for the diagnosis of advanced fibrosis were obtained using receiver operating characteristic analysis in patients with biopsy‐confirmed non‐a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 51 publications
0
46
0
Order By: Relevance
“…In Europe, the ELF (enhanced liver fibrosis) test, involving hyaluronic acid and a tissue inhibitor of matrix metalloproteinase type 1 (TIMP-1) along with P3NP (aminoterminal propeptide of type 3 procollagen) is used as the second step [41] (Table 1). A validation study for the efficacy of ELF test was conducted in Japan [42]. In Japan, liver fibrosis markers such as type IV collagen 7S and Mac-2 binding protein glycosylation isomer (M2BPGi) are generally used by hepatologists.…”
Section: Non-invasive Diagnostic Methods For Liver Fibrosismentioning
confidence: 99%
“…In Europe, the ELF (enhanced liver fibrosis) test, involving hyaluronic acid and a tissue inhibitor of matrix metalloproteinase type 1 (TIMP-1) along with P3NP (aminoterminal propeptide of type 3 procollagen) is used as the second step [41] (Table 1). A validation study for the efficacy of ELF test was conducted in Japan [42]. In Japan, liver fibrosis markers such as type IV collagen 7S and Mac-2 binding protein glycosylation isomer (M2BPGi) are generally used by hepatologists.…”
Section: Non-invasive Diagnostic Methods For Liver Fibrosismentioning
confidence: 99%
“…The use in serial combination of TE, NFS and FIB-4 in patients in the grey area of the first test or in those with high values of liver median stiffness (> 9.6 kPa) or low NFS or FIB-4 value (< -1.45 and < 1.3 respectively), increased the diagnostic performance and reduced the diagnostic uncertainty area compared to the use of these tests alone [122]. The combination of ELF test and TE has shown higher diagnostic accuracy for the diagnosis of AF (Sp 97.9%) compared to ELF test alone (Sp 90.6%) [124]. The FibroScan-AST (FAST) score is a novel model (composed of Liver Median Stiffness, controlled attenuated parameter and AST), that showed a good diagnostic performance in identifying NASH with a Nash Activity Score > 4 + F > 2 with a PPV of 0.83-0.81 and an NPV of 0.85-0.71, respectively in derivation and validation cohort [125].…”
Section: Us-based Imagining Technique Tementioning
confidence: 97%
“…24 Other studies have confirmed the accuracy of the ELF score in the assessment of hepatic fibrosis in PLWH and in those with NAFLD. [25][26][27][28] Assuming the SD of the ELF score is 1.12, with 20 patients in each group for the analysis, a difference in ELF of 1 point can be estimated with a 95% CI from 0.6 to 1.4. Assuming an attrition rate of 33%, a target of 30 individuals will be recruited per group.…”
Section: Post-trial Carementioning
confidence: 99%